2016
DOI: 10.1108/ijes-09-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Hostility in firefighters: personality and mental health

Abstract: Purpose – The purpose of this paper is to investigate the contribution of personality factors, especially hostility, as they related to traumatic stress and mental health symptoms in firefighters. Design/methodology/approach – A group of paid-professional firefighters (n=94) completed a questionnaire study that included a demographic questionnaire, the Impact of Event Scale-Revised, the NEO Five-Factor Inventory-Revised, the Framingham T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…While the subjective appraisal of a potentially traumatic event is a relevant factor for the development of stress-related diseases, or the protection against them, social support is directly related to the way of looking at life and, consequently, to the perception of stress [41][42][43]. The current survey revealed that the presence of social support not only protects against the development of stress-related diseases, but also attenuates the association of stress-related symptoms with suicidal ideation by influencing the subject's interpretation of the event and the choice of coping strategies [11].…”
Section: Social and Organizational Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…While the subjective appraisal of a potentially traumatic event is a relevant factor for the development of stress-related diseases, or the protection against them, social support is directly related to the way of looking at life and, consequently, to the perception of stress [41][42][43]. The current survey revealed that the presence of social support not only protects against the development of stress-related diseases, but also attenuates the association of stress-related symptoms with suicidal ideation by influencing the subject's interpretation of the event and the choice of coping strategies [11].…”
Section: Social and Organizational Supportmentioning
confidence: 99%
“…Subjective perception, in addition to being built throughout the individual's development, is also influenced by relationships and cultural and social contexts. Appraising the aspects of the subjective perception, the importance of social and organizational support is justified as contributing to the way in which an individual interprets and deals with adversities, as well as the perception of being supported may reduce the levels of stress [30,42,43,45].…”
Section: A Relational Model For Stress In Firefightersmentioning
confidence: 99%
“…Given its civic importance, and the transitions taking place therein, emergency services represent an important area for examination corning how 'extreme' situations unfold in relation to everyday contexts. Extant literature on the emergency services has considered a number of prevalent issues and topics including: network structures and command systems (Griffith and Roberts 2015); culture change (Wankhade et al 2018); performance (Barton & Beynon 2012); decision-making (Shaw et al 2013); inter-professional collaboration (Collin et al 2015); leadership dynamics (Van Wart 2014); and mental health (Wagner et al 2016). Much of this work has generally concentrated on a functionalistic frame of reference typically focusing on issues of efficiency and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies conducted on firefighters analyzed the influence of personal characteristics of the individual, social and/or marital circumstances in isolation, but failed to consider the combined influence of these factors on health and satisfaction. The one study analyzing hostility in firefighters conducted by Wagner et al (2016), reporting increased levels of neuroticism and hostility, warrants enough support for further investigation. The present study proposes a joint analysis of individual traits, workplace characteristics, and work-family interaction that can serve as environmental audits of the factors that represent significant stressors for firefighters.…”
Section: Chapter Three: Key Gaps In the Literaturementioning
confidence: 99%
“…The present study used Social Ecology Theory to derive the hypotheses to be tested and, therefore, aimed to further explore if and how personality, spousal relationship, and social factors mediate the relationship between work and health for firefighters. Given previous research completed with paramilitary samples Wagner et al, 2010, Wagner et al, 2016, the general expectation holds that firefighters would score high for hostility and report increased overall dissatisfaction, stress, and health issues. By reporting low levels of overall satisfaction, decreased job satisfaction, marital satisfaction and life satisfaction, one would expect individuals scoring high on hostility to negatively react to work related stressors, experience negative affective emotions, and isolate themselves from co-workers and family.…”
Section: Questions For Investigationmentioning
confidence: 99%